Optimization of Dielectric Excitation for Metal Oxide Sensors: Simulation and Experimental Results - Alessandro Benegiamo; Meryl Cruz; Stefano Robbiani; Raffaele Dellacá; Santiago Marco (Proceedings)
This study assesses the agreement in terms of linearity errors between simulated and experimental data from MOX sensors operated in dielectric excitation mode. Both simulated and experimental reactance spectra exhibit high linearity with respect to gas concentration in the high-frequency shoulder of the relaxation peak. The results demonstrate strong agreement between simulated and experimental 95% CI of absolute linearity errors as a function of frequency. As expected, the empirical errors are slightly bigger compared to the simulation prediction, since the latter only considers the linearity errors. The good correspondence between simulations and empirical results supports the use of simulation to optimize the tuning capacitor and the selection of the optimal operating frequency.